Preclinical Assessment of Viral Vectored and Protein Vaccines Targeting the Duffy-Binding Protein Region II of Plasmodium Vivax - de Cassan, Simone C.; Shakri, A. Rushdi; Llewellyn, David; Elias, Sean C.; Cho, Jee Sun; Goodman, Anna L.; Jin, Jing; Douglas, Alexander D.; Suwanarusk, Rossarin; Nosten, François H.; Rénia, Laurent; Russell, Bruce; et al. (Frontiers in Immunology, 2015)
Malaria vaccine development has largely focused on Plasmodium falciparum; however, a reawakening to the importance of Plasmodium vivax has spurred efforts to develop vaccines against this difficult to treat and at times severe form of relapsing malaria, which constitutes a significant proportion of human malaria cases worldwide. The almost complete dependence of P. vivax red blood cell invasion on the interaction of the P. vivax Duffy-binding protein region II (PvDBP_RII) with the human Duffy antigen receptor for chemokines (DARC) makes this antigen an attractive vaccine candidate against blood-stage P. vivax. Here, we generated both preclinical and clinically compatible adenoviral and poxviral vectored vaccine candidates expressing the Salvador I allele of PvDBP_RII – including human adenovirus serotype 5 (HAdV5), chimpanzee adenovirus serotype 63 (ChAd63), and modified vaccinia virus Ankara (MVA) vectors. We report on the antibody and T cell immunogenicity of these vaccines in mice or rabbits, either used alone in a viral vectored prime-boost regime or in “mixed-modality” adenovirus prime – protein-in-adjuvant boost regimes (using a recombinant PvDBP_RII protein antigen formulated in Montanide®ISA720 or Abisco®100 adjuvants). Antibodies induced by these regimes were found to bind to native parasite antigen from P. vivax infected Thai patients and were capable of inhibiting the binding of PvDBP_RII to its receptor DARC using an in vitro binding inhibition assay. In recent years, recombinant ChAd63 and MVA vectors have been quickly translated into human clinical trials for numerous antigens from P. falciparum as well as a growing number of other pathogens. The vectors reported here are immunogenic in small animals, elicit antibodies against PvDBP_RII, and have recently entered clinical trials, which will provide the first assessment of the safety and immunogenicity of the PvDBP_RII antigen in humans.